Microwave assisted preparation of Eu2+-doped Åkermanite Ca2MgSi2O7 - Birkel, Alexander; Darago, Lucy E.; Morrison, Alasdair; Lory, Laurianne; George, Nathan C.; Mikhailovsky, Alexander A.; Birkel, Christina S.; Seshadri, Ram (Solid state sciences, 2012)
A rapid and energy efficient microwave assisted solid state preparative route for europium-doped Åkermanite (Ca2MgSi2O7) has been developed. This method reduces the reaction time and energy needed by more than 90%, compared to the preparation carried out in a conventional furnace. The obtained samples are phase pure as has been determined using synchrotron X-ray powder diffraction data and Rietveld analyses. Scanning electron microscopy was employed to investigate the morphology of the microwave prepared compounds whilst energy dispersive X-ray spectroscopy (EDX) was used to verify the elemental composition of the specimens. A systematic investigation of the influence of the utilized microwave setup is presented. Finally, the microwave prepared materials were subject to temperature dependent photoluminescence measurements in order to investigate the thermal quenching of the luminescence. [Display omitted] ► Eu-doped Ca2MgSi2O7 has been prepared by a microwave assisted synthesis. ► The influence of some important experimental parameters has been examined. ► Phase pure materials have been obtained in less than one hour.